The Influence of Paramedic and Patient Gender on the Administration of Analgesics in the Out-of-Hospital Setting. (3rd April 2014) - Lord, Bill; Bendall, Jason; Reinten, Tracie
Abstract Objective. To determine whether analgesic administration in the out-of-hospital setting is influenced by the gender of the patient or the gender of the paramedic. Methods. This retrospective cohort study of patient care records included adult patients (age > 15 years) with moderate to severe pain (verbal numerical rating score 4–10) treated by paramedics between January 1, 2008 and December 31, 2009. Data extracted included patient pain severity score, analgesia provided by paramedics, and gender of the treating paramedic. Data was analyzed by descriptive statistics, χ2 test, and logistic regression. The primary outcome measures were the effect of patient and paramedic gender on analgesic administration. Results. The study population comprised 42, 051 patients, median age of 57 years (38–75); 50.4% were female and 51% were administered an analgesic agent. For the outcome of receiving any analgesia, neither patient gender nor paramedic gender was predictive (p = NS). In a multivariate model for the outcome of receiving any analgesia, patient gender, paramedic gender, and the interaction between patient and paramedic gender were all nonsignificant (p = NS). For the outcome of receiving opioid analgesia (i.e., morphine or fentanyl), male patients were at greater odds of receiving an opioid (OR 1.52, 95% CI 1.29–1.79, p < 0.0001). Paramedic gender was not predictive of whether an opioid was given (p = NS). Conclusions. The gender of the paramedic did not appear to influence the odds of analgesic administration. Female patients were less likely to receive opioids. Paramedic gender does not explain this finding.